Pengaruh Suplementasi Zinc dan Vitamin C terhadap Pasien Malaria yang Anemia - Januar Ishak Hutasoit; Intanri Kurniati (Medula, 2020)
Malaria is one of disease that has a high incidence in Indonesia. This disease is caused by the Plasmodium parasite which can attack and damage red blood cells. Things that can occur in patients infected with Plasmodium are anemia. Anemia is a condition where there is a decrease in hemoglobin and erythrocyte levels in the blood. Anemia that occurs in malaria generally is normocytic, normochromic, and hemolytic anemia. Hemolytic anemia occurs because of the process of hemolysis, which is an increase in destruction of erythrocytes or premature breakdown of erythrocytes. Vitamin C and Zinc are known as minerals that can help iron activity. Iron is included in the formation of hemoglobin, but in malaria patients giving iron tablets can worsen the patient's condition, therefore it is done giving vitamin C and Zinc in preventing and helping to overcome anemia in malaria patients.